A glassy carbon electrode modified with tailored nanostructures of cobalt oxide for oxygen reduction reaction - M. M., Shahid; Zhan, Yiqiang; Alizadeh, Mahdi; Sagadevan, Suresh; Paiman, Suriati; Oh, Won Chun (Elsevier, 2020)
Herein we report on various surface morphological characteristics of the synthesized cobalt oxide (Co3O4) nanostructures obtained by means of facile one-step hydrothermal method for oxygen reduction reaction (ORR). The synthesized nanostructures of Co3O4 were adequately characterized by field emission scanning electron microscopy (FESEM) fitted with Energy-dispersive X-ray spectroscopy (EDX) elemental mapping, X-ray diffraction (XRD) and Raman techniques. The electrochemical studies were carried out to analyse the performance of as-synthesized catalysts for ORR by cyclic voltammetry (CV), and chronoamperometric (CA) techniques. A higher electrocatalytic response was observed for Co3O4 nanocubes compared with all the other controlled electrodes by CV with a current density of 0.69 mA/cm2 at a potential value of −0.46 V. The as-synthesized material showed adequate tolerance against methanol observed by CV in the presence of 0.5 M methanol, and good stability when compared with commercial Pt/C catalyst using the CA technique.